The Influence of the Alkaline Activator on the Life Cycle Assessment of Alkaline Activated Natural Pozzolan Geopolymers Concrete - Kamil, Marwah (2020)
This paper studies the effectiveness of replacing cement in concrete with natural pozzolan, originated from Saudi Arabia, on the reduction of the harmful gasses, carbon dioxide equivalent gases, during the production process of the concrete. Life cycle assessment is done on the alkaline activated natural pozzolan geopolymer concrete, global warming potential of 100 years GWP100 category. The life cycle assessment exercise was also done on alkaline activated natural pozzolan geopolymers where the natural pozzolan was activated with different types of alkaline activator to reduce the GWP100 of the geopolymer concrete even further. The results of the study showed that the geopolymer with natural pozzolan activated by sodium hydroxide and sodium silicate have the lowest GWP100 of 106 kg..eq, which is lower than that of the PC concrete by 72%. Also, it is found that the alkaline activator is responsible for the largest amount of the carbon dioxide equivalent gases produced during the production of 1 of the geopolymer concrete. Two further life cycle assessment exercises were done to replace the sodium silicate alkaline activator with sodium hydroxide and silica extracted from rice husk ash. The results of the life cycle assessment, GWP100 category, showed that both geopolymer concretes have higher GWP100 than that of the natural pozzolan activated with sodium hydroxide and sodium silicate. The GWP100 of the natural pozzolan alkaline activated by sodium hydroxide geopolymer and natural pozzolan activated by sodium hydroxide and silica extracted from rice husk ash are 114 kg..eq and 197 kg..eq respectively. However, all of the alkaline activated natural pozzolan geopolymer concrete showed GWP100 less than that of the PC concrete by at least 48%. The results of the life assessment exercise are then compared to life cycle assessment exercises done by other researchers on alkaline activated natural pozzolan geopolymer concrete as well as other types of geopolymer concretes. The recommendations of this study is that further research needs to be conducted to study the properties of the alkaline activated natural pozzolan geopolymer concrete and further life cycle assessments need to be conducted on different mix design option on both raw and calcinated natural pozzolan to encourage the consultants and contractors to replace cement with more sustainable and durable material like the natural pozzolan.